Entrepreneurial orientation of SMEs in Labuan and its effects on performance - Ricardo, Baba; Sunmuglvadivu, Elumalai (Faculty of Economics and Business, 2011)
Entrepreneurial orientation (EO) has been defined as the measure of firm level entrepreneurship. EO has been linked with organizational performance, whereby the higher the EO, the higher the level of performance. The EO is deemed as a multidimensional construct encompassing five dimensions e.g. autonomy, risk taking, innovation, pro-activeness, and competitive aggressiveness. Thus this study investigates the relationship between EO dimension and organizational performance indicators e.g. product performance, customer performance and sales growth among SMEs in Labuan. A total of 101 SMEs were selected and these establishments were involved in service related business, retail business and also wholesale. The study concludes that risk taking, innovation, pro-activeness and competitive aggressiveness have significant positive relationship with organizational performance. Meanwhile no relationship is found between autonomy and SME performance. Finally based on the various strength of relationship exhibited by the EO dimensions, this study also concludes that EO is a multidimensional construct and that these dimensions vary independently.